A inserç\~ao da Coreia do Sul na cadeia global automobilística: Foco sobre as políticas públicas - Uallace Moreira Lima (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The auto industry, since the 1960s, showed substantial growth in South Korea causing the country at the end of the 1980s was among the world's leading manufacturers of automobiles. In the early 1990s, associated with the opening up of the economy held by the Korean government, the auto industry begins to present problems that will become more evident in the Asian economic crisis in 1997, leading the government to adopt an industry rationalization policy promoting a process of mergers and acquisitions, as well as allowing the entry of foreign investors in the automotive industry. Reforms and changes in the Korean auto industry just beginning to be realized when, from a global point of view, there is a process of internationalization of production in which companies seek new strategies for entering the values of Global Chains (GVCs), where many industries out the condition of nationally bounded entities to the condition of fragmented and globally distributed business networks. This research aims to investigate the changes that passed the automotive industry in recent years from the perspective of the strategies of Korean companies in GVCs, analyzing public policies implemented by the government and Korean companies for insertion in GVCs.
Keywords: F02; F15; L62; L00; L2; O3; O21; O22; 330; global values chains; automobile industry; value added